Union Effects on Municipal Employment and Wages: A Longitudinal Approach - Valletta, Robert G. (Journal of Labor Economics, 1993)
This article examines municipal union employment and wage effects in a sample of police, fire, sanitation, streets and highways, and finance and control departments from approximately 900 U.S. cities during 1977-80. Cross-section results for 1980 suggest positive union contract effects on fire fighter and sanitation employment and wages, consistent with demand shifts due to union political influence in municipal bargaining. I then model potential omitted variables as nonstationary fixed effects and apply longitudinal models to estimation of employment and wage changes between 1977 and 1980. The longitudinal results provide little support for the demand shift hypothesis.